Reducing the Mobility of SARS-CoV-2 Variants to Safeguard Containments - Martin Hellwig; Viola Priesemann; Guntram B. Wolff (Intereconomics, 2021)
Escape variants can cause new waves of COVID-19 outbreaks and put vaccination strategies at risk. To prevent or delay the global spread of these waves, virus mobility needs to be minimised through screening and testing strategies, which should also cover vaccinated people. The costs of these strategies are minimal compared to the costs to health, society and the economy from another wave.
Keywords: 330; Coronavirus; Epidemie; Infektionsschutz; Impfung